Design, Fabrication and Performance Analysis of a Portable, Antenna Analyzer Based, Quartz Crystal Microbalance Measuring System with Energy Dissipation - Kirimli, Ceyhun Ekrem (Fırat University, 2024)
Impedance measurements play a critical role in analyzing the electrical behavior of piezoelectric biosensors in general. Antenna analyzers are engineered to measure the specific case of input impedance for antenna systems. In this study small form factor antenna analyzer is repurposed to work as driving circuit for a Quartz Crystal Microbalance (QCM) biosensor in combination with a single board computer as an indication of how small and portable an impedance measuring system can be made, while allowing monitoring of important parameters of series and parallel resonance frequencies together with dissipation factor. A QCM crystal with a 10 MHz fundamental resonance frequency is employed to determine the limit of detection of the system in Bovine Serum Albumin (BSA) and glycerol solutions. Dissipation factor and phase angle were monitored during the experiments. Limit of detection is 20 µg/ml BSA in phosphate buffer saline (PBS) and 250 µl of glycerol in 100 ml of deionized water.

Empedans ölçümü birçok piezoelektrik biyosensörün elektriksel davranışını analiz etmede kritik rol oynayan bir tekniktir. Anten analizörleri, anten sistemlerinin giriş empedansını ölçmek için tasarlanmıştır. Bu çalışmada bir empedans ölçüm sisteminin ne kadar küçük ve taşınabilir olabileceğinin bir kanıtı olarak, tek kartlı bir bilgisayarla kombinasyon halinde bir Kuvars Kristal Mikro Terazi (QCM) biyosensörü için sürüş devresi olarak çalışmak üzere küçük form faktörlü bir anten analizörü yeniden tasarlanmiştır. Seri ve paralel rezonans frekanslarının ve dağılım faktörünün önemli parametrelerinin izlenmesi 10 MHz temel rezonans frekansına sahip bir QCM kristali, sistemin Bovine Serum Albumin (BSA) ve Gliserol çözeltilerinde tespit limitini belirlemiştir. Deneyler sırasında dağılım faktörü ve faz açısı izlenmiştir. Saptama sınırı, fosfat tamponlu salinde (PBS) 20 µg/ml BSA ve 100 ml deiyonize suda 250 µl gliseroldür.
Enerji Yitimi Ölçebilen Taşınabilir Anten Analizörü Tabanlı Kuvars Kristal Mikroterazi Ölçüm Sisteminin Tasarımı, Üretimi ve Performans Analizi
Keywords: Biomedical Diagnosis; Biyomedikal Tanı; Medical Devices; Tıbbi Cihazlar